Surgery do save life in cervical spinal injury: 5 years study of a tertiary care in East Java, Indonesia - Pratamanugroho, Ilham; Agung Irianto, Komang; Widhiyanto, Lukas; Lestari, Pudji (Edelweiss Applied Science and Technology, 2024)
Cervical spine has the most movement in spine therefore it has high risk of injury which may involve vertebrae, soft tissue and spinal cord. Trauma to cervical has highest risk of neurologic deficits due to spinal cord injury (SCI) causing high number of morbidity and mortality. Retrospective study was conducted with descriptive-analytic design by total sampling of cervical spinal injury patients in Dr. Soetomo General Academic Hospital from January 2018 to June 2023. Patient demographic and survival analysis of patients was described using Kaplan-Meier chart and logistic regression test to find factors contributing to patients’ survival. Gender, age, mechanism of injury, surgical approach, duration, intra-operative bleeding, lesion level, time to surgery, and initial blood laboratory had no significant impact while neurological status and operative treatment have significant survival probability. Patients with American Spinal Injury Association Impairment Scale (AIS) A score have lower survival rate which associated with respiratory muscle weakness, cardiovascular and autonomic nervous system dysfunction. Any unstable cervical fracture is advised for surgery while decompression surgery is recommended for improving outcome and ease of rehabilitation. Clinical implication of this study recommends surgery for cervical spinal injury with 5.6 times more chance of survival than non-operative patients. Initial AIS neurological status and surgery performed contributes to survival. Level of cervical lesion, age, gender, mechanism of injury, surgical approach, duration, blood laboratory tests do not have a significant impact on survival while fastest time admission to surgery does not reflect higher chance of survival probability.